UMP contributes 10 thousand pieces of medical gloves to a hospital at Hebei University, China - Fatin Zahirah, Mansur (2020)
Universiti Malaysia Pahang (UMP) contributed 10 thousand pieces of medical gloves to a hospital at Hebei University, China, due to the outbreak of coronavirus or also known as Covid‐19.